SUPERVISORY MECHANISMS IN CONSUMER PROTECTION FOR FLIGHT DELAYS (COMPARATIVE STUDY: INDONESIA AND MALAYSIA) - Agus Mahardika; Ema Nurkhaerani (RADJA PUBLIKA, 2026)
Flight delays remain a recurring issue that harms air transport consumers in both Indonesia and Malaysia. This study aims to comparatively analyze the consumer protection oversight mechanisms for flight delays in both countries in order to formulate an ideal supervisory model. The research employs a normative juridical method with statutory, conceptual, and comparative approaches, analyzed through Philipus M. Hadjon's theory of preventive legal protection and Lawrence M. Friedman's legal system theory. The findings show that oversight in Indonesia under PM 89/2015 remains administrative-reactive and involves multiple institutions (DJPU, BPKN, BPSK), while Malaysia's MACPC 2016 applies a more preventive and integrated continuous compliance monitoring system through MAVCOM/CAAM. The study recommends an ideal supervisory model for Indonesia that integrates administrative, operational, and continuous compliance oversight, supported by risk-based supervision and financial sanctions, to strengthen consumer rights protection preventively and sustainably.